Development of a Web-based SIWES Logbook Management System with Secure Authentication and Role-based Access: A Case Study of Federal University of Technology, Akure, Ondo State - Afolayan, A. H.; Onoriode, T. M. (Journal of Science, Technology and Innovation Research, 2025)
The Student Industrial Work Experience Scheme (SIWES) is designed to connect classroom learning with real-world workplace experience across Nigerian universities. A central component of this process is the logbook, which students use to record their daily tasks and on which supervisors rely for evaluation. In many Nigerian institutions, these logbooks are still kept on paper, a familiar practice that often leads to delays, lost records, and other inefficiencies. To address these challenges, this study aims to design and implement a secure, role-based, multi-user, web-enabled SIWES logbook system to streamline documentation, supervision, and evaluation, with the objectives of improving accessibility, enhancing security through authentication, and enabling real-time monitoring for all stakeholders. The system was developed using the Waterfall Software Development Life Cycle (SDLC) and a four-tier architecture comprising a React.js presentation layer, Node.js application layer, MySQL data layer, and a security layer employing Bcrypt for password hashing and JSON Web Tokens (JWT) for stateless authentication, alongside Role-Based Access Control (RBAC) for tailored permissions. A user evaluation with 40 participants at the Federal University of Technology, Akure, demonstrated high usability, security, and adoption: 65% were very satisfied, 72.5% found navigation easy, 57.5% rated the system as very secure, and 95% preferred it over paper-based logbooks. These findings confirm that the proposed system enhances monitoring, ensures data integrity, and provides timely feedback, offering a practical, centralized, and secure alternative to traditional SIWES logbooks.